Estudio de factibilidad para reemplazar la gestión de devolución de llamadas por mensajes de texto en el servicio integrado de seguridad Ecu 911 - Pinto Bastidas, Carolina Alejandra (2018)
SIS ECU 911 manage the Emergency Unique Number 9-1-1 in the country, which carries out an internal procedure to raise awareness of citizenship, about the correct use of the 9-1-1 line, through a callback, process that is necessary, but, it affect the 9-1-1 line availability, time of operational staff and high costs for the institution. That is why it performs the present study, to replace the callback by automatic sending of text messages that reach users to achieve institutional goals.